Associations Between Work-Related Factors and Psychological Distress Among Construction Workers. Issue 12 (7th December 2021) - Dennerlein, Jack T.; Eyllon, Mara; Garverich, Suzanne; Weinstein, Daniel; Manjourides, Justin; Vallas, Steven P.; Lincoln, Alisa K.
Abstract : Supplemental Digital Content is available in the text Abstract : Objective: Identify work-related factors associated with the mental health and well-being of construction workers. Methods: We completed eight key informant interviews, six worker focus groups, and a survey, informed by the interviews and focus groups, of 259 construction workers on five construction sites. Negative binomial regressions examined associations between psychological distress and work-related factors including safety climate, work-to-family conflict, psychological demands, social support, harassment, and job security. Results: Three themes emerged from the interviews and focus groups, job demands and structure, social support and workplace relations, and job precarity. From the survey higher psychological demands, higher work-to-family conflict, lower supervisor support, higher discrimination, and higher likelihood of losing a job were associated with higher psychological distress. When combined into a single model job demands and work-to-family conflict remained significant. Conclusions: Work-related factors were associated with high levels of distress.